Correlation of body mass index and waist/hip ratio with severity of coronary artery disease - Bhatia, Ritu; Bhatia, Ansh; Ganatara, Keya (International Journal of Research in Medical Sciences, 2022)
Background: Obesity assessed by body mass index (BMI) and waist/hip ratio (WHR) are better predictors of cardiovascular disease. However, there is a dearth of data investigating the correlation of BMI and WHR with severity of CAD, particularly among the Indian population. This study aims to investigate the correlation of BMI and WHR with severity of CAD assessed by angiography. Methods: This open-label observational study included patients who underwent angiography, angioplasty, or coronary artery bypass grafting in the past one month. All data such as age, gender as well as anthropometric measurements such as height (meters), weight (kg), and waist circumferences (cm), and hip circumferences (cm) were collected at the first follow-up visit. BMI (kg/m2), body surface area (BSA) (m2), and WHR were calculated. Angiography findings were retrieved from the patient’s own record to note the severity of CAD. Results: In total, 302 patients were analyzed. The mean age of the study sample was 60.5±11.5 years, and 71.9% were males. Mean BMI, BSA, and WHR were 27.0±4.3 kg/m2, 1.3±0.8 m2 and 0.96±0.07, respectively. BMI was not significantly correlated with severity of CAD (p=0.051). In both male and female patients, WHR was not significantly correlated with severity of CAD (male: p=0.256 and female: p=0.851). Conclusions: It has been concluded that BMI and WHR were not significantly correlated with severity of CAD in an Indian population.